TIGA UNSUR GAYA DALAM NOVEL SEBELAS PATRIOT KARYA ANDREA HIRATA DAN KELAYAKANNYA SEBAGAI BAHAN AJAR BAHASA DAN SASTRA INDONESIA DI SEKOLAH MENENGAH ATAS (SMA) - yoga irawan; munaris munaris; edy suyanto (FKIP Universitas Lampung, 2013)
The research problems in this research is about the appropriateness of three elements of style (diction, figurative language, imageri) in Andrea Hirata’s novel entitled Sebelas Patriot as teaching learning material of Indonesian language and literature at first year student of senior high school. This research aims to describe the appropriateness of those three elements of language style as the language learning material in senior high school. The data of the research was taken by Andrea Hirata’s novel entitled Sebelas Patriot. The research method in this research was descriptive qualitative research design. In which the data was taken by the process of read a whole novel’s content, take a note, and identify the three language elements. Furthermore, the researcher analyzed and concluded the data of analysis result to find out whether or not Andrea Hirata’s entitled Sebelas Patriot can be included as the learning material for Indonesian language and literature at the senior high school level. The results of the research showed that the foreign diction was dominated by the England diction, due to the England football popularity. Nowadays, the term in English football was really familiar with the Indonesian football lovers because those people considered that football was come as the nature of England. Figurative language was dominated by the comparison of figurative language in which simile took the first place in figurative language usage. Meanwhile, antonomasia, paradoks, paralelisme, tropen came as the less usage of figurative language. It can be caused by the aims of the author whose refers to compare the similar things to the comparison object. Imagery in this novel was imagery in vision, audio, and palpability. The most useful imagery was imagery vision and imagery of palpability was the less one. It can be probably caused due to the author’s desire in taking the audience falling for the novel’s setting. Due to the highly relation of diction studies namely diction, figurative language, and imagery towards the language learning material at first year students’ of senior high school in Indonesian language and literature. Thus, the teacher can use the Andreas Hirata’s novel entitled Sebelas Patriot as language learning material since it provides the diction usage of figurative language and imagery. In shorts, since the learning materials was appropriate to the language and literature in language aspects. It can concludes that Andrea Hirata’s Sebelas Patriot is appropriate to be the alternative teaching learning material of Indonesian language and literature at the first year students of senior high school especially in the intrinsic aspects namely language style.Keyword: novel, appropriateness, element of style